Old Medical Books in Edinburgh Libraries: The Royal Medical Society Catalogue Project - Hargreaves, Geoffrey (Res Medica, 2014)
In the justifiable belief that the older collections of printed medical books in Edinburgh libraries are exceptional in both quality and quantity, the Royal Medical Society has initiated a scheme for the production and, it is hoped, the publication of a composite catalogue of these collections for the benefit of scholars in the history of medicine and science. The institutions currently involved in the scheme are the National Library of Scotland, the Royal Botanic Garden, the Royal College of Physicians, the Royal College of Surgeons, the Royal Observatory, the Royal Society and the University of Edinburgh (including New College). In addition, the Royal Medical Society is, of course, contributing its own residual but important collection of older books withheld from the 1969 sale as being unrepresented in any other Edinburgh collection. The quality of the Edinburgh collections as a whole may perhaps be adequately suggested by noting their strength in the classics of medical literature. There are, for example, three copies of the De medicina (1478) of A. Cornelius Celsus, one of the first general medical treatises to be printed; four copies of the herbal De historia stirpium (1542) of Leonhard Fuchs, and three of the anatomical work De humani corporis fabrica ( 1543 ) of Andreas Vesalius — books which, particularly through the quality of their illustrations, did much to release the study of medical botany and anatomy "from traditional inaccuracies; one of the three known copies of the Christianissimi restitutio (1553) of Michael Servetus, which includes the first Western account of the lesser circulation; no fewer than five copies (including one with the errata) of what is generally regarded as the most important work in the history of medicine, William Harvey’s account of the circulation in his De motu cordis (1628); five copies (including a presentation copy with the plate in colour) of another classic of medical botany, William Withering’s An account of the foxglove (1785); and a copy of Sir Charles Bell’s exceptionally rare Idea of a new anatomy of the brain (1811), a pamphlet even more unprepossessing in appearance than the De motu cordis, yet — in the context of the nervous system — of comparable importance as an advance in medical knowledge.